1987
DOI: 10.1143/jjap.26.l447
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Antiferromagnetic Ordering in La2CuO4

Abstract: Neutron diffraction study on La2CuO4, which is the basic material of high-T c oxide superconductors, revealed the antiferromagnetic ordering in this compound. The value of the magnetic moment is 1.1±0.3 µB per copper atom, and the Néel temperature was found to be 240±10 K from temperature dependence of the intensity of the magnetic reflection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…The existence of Sr 2 CuO 2 Cl 2 has also been well-known since 1970s. , Vaknin et al reported that a three-dimensional antiferromagnetic structure is identified below the Néel temperature T N = 251 K by neutron diffraction. This T N is similar to that for La 2 CuO 4 ( T N ∼ 250 K). , Theoretical studies of its electronic structure predicted that proper hole doping (0.35−0.38 per Cu) into Sr 2 CuO 2 Cl 2 would induce superconductivity with T c around 25 K. , Hiroi et al reported that a similar way of hole doping to the case of Ca 2 CuO 2 Cl 2 , i.e., sodium and potassium substituting for calcium, does not work for Sr 2 CuO 2 Cl 2 .…”
Section: Oxychloride (X = Cl)supporting
confidence: 59%
“…The existence of Sr 2 CuO 2 Cl 2 has also been well-known since 1970s. , Vaknin et al reported that a three-dimensional antiferromagnetic structure is identified below the Néel temperature T N = 251 K by neutron diffraction. This T N is similar to that for La 2 CuO 4 ( T N ∼ 250 K). , Theoretical studies of its electronic structure predicted that proper hole doping (0.35−0.38 per Cu) into Sr 2 CuO 2 Cl 2 would induce superconductivity with T c around 25 K. , Hiroi et al reported that a similar way of hole doping to the case of Ca 2 CuO 2 Cl 2 , i.e., sodium and potassium substituting for calcium, does not work for Sr 2 CuO 2 Cl 2 .…”
Section: Oxychloride (X = Cl)supporting
confidence: 59%
“…In powder diffraction, the structural superlattice peaks are weak, but significantly more prominent than the magnetic peaks, which are smaller than the background [46]. An early diffraction study mis-identified the structural peaks as antiferromagnetic peaks [47]. The use of polarized neutron diffraction eventually confirmed the proper identification [48].…”
Section: Magnetic Structurementioning
confidence: 99%
“…The antiferromagnetism was detected there in the studies of susceptibility [21], neutron scattering [22][23][24] and μSR [25,26]. In μSR studies the magnetic ordering was seen as spontaneous oscillations in zero-field experiments.…”
Section: "214"mentioning
confidence: 95%